Α Simple Method for the Determination of Lacosamide in Blood by GC‐MS. Issue 1 (27th August 2019) - Mouskeftara, Thomai; Alexandridou, Anastasia; Krokos, Adamantios; Gika, Helen; Mastrogianni, Orthodoxia; Orfanidis, Amvrosios; Raikos, Nikolaos
Abstract: Lacosamide is a functionalized amino acid with antiepileptic function. Therapeutic drug monitoring (TDM) in patients for lacosamide is critical as it allows clinicians to control epileptic seizures. A single liquid–liquid extraction step was applied for the extraction of lacosamide from whole blood samples which were thereafter analyzed by GC‐MS. Optimum extraction conditions were selected on the basis of experiments with various solvents at different pHs, indicating ethyl acetate at pH 12 as the most efficient parameters for the extraction of lacosamide. Method exhibited linearity from 2 to 100 μg/mL with R 2 = 0.998. Accuracy and precision were evaluated at three concentrations and found to be within acceptable limits. LOD and LOQ were determined at 0.1 and 0.5 μg/mL, respectively. Lacosamide was found to be stable at storage conditions. The developed method was applied successfully in clinical samples and postmortem blood sample from an overdose case.